Intervening by staying professional: How Nordic environmental journalists make sense of their roles - Hujanen, Jaana; Jangdal, Lottie; Dovbysh, Olga; Andersen, Ida Vikøren; Kolbeins, Guðbjörg Hildur; Lehtisaari, Katja; Oivo, Teemu (Nordicom Review, 2024)
The notion of intervention is gaining traction among Western environmental journalists. While existing research has predominantly focused on countries outside the Nordic region, in our study we investigate the self-perceptions of professional journalists in the Nordic countries of Finland, Iceland, Norway, and Sweden. Through semi-structured interviews, we examine the roles that Nordic journalists construct when reflecting on covering the environmental beat, paying particular attention to how they make sense of the idea of intervening – that is, their involvement in interpreting, making sense of, and engaging the public in environmental issues. Using thematic qualitative analysis to analyse the interviews, we have identified four journalistic roles: 1) objective news provider, 2) critical watchdog, 3) sense-maker and educator, and 4) environmental advocate. Our findings suggest that Nordic journalists intervene by adhering to professional norms and practices and renegotiating them. While the role of objective news provider remains prominent among Nordic journalists, it is intertwined with various forms of intervention across all identified roles. Peer reviewed